COST EFFECTIVENESS OF SCREENING OF ALL NEWLY RECRUITED EMPLOYEES FOR DIABETES AT A TERTIARY CARE HOSPITAL - Ali, Niloufer Sultan; Khuwaja, Ali Khan (Journal of Ayub Medical College Abbottabad, 2007)
Background: Diabetes Mellitus is a disease which remains asymptomatic for long duration of time and usually diagnosed either when gets complicated or by routine or opportunistic screening. The practice of universal screening is not recommended, particularly in constraint resources. However, we embarked with a study to assess the yield of recommended screening f or Type 2 diabetes in all the newly recruited employees at a tertiary care hospital in Karachi. Methods: All the information required for this study was collected from medical records of all newly recruited employees of nursing services department of a tertiary care hospital of Karachi, Pakistan, over a period of 5 months (August 2004 to December 2004). Out of 360 subjects , 326, whose information was found to be complete, were included for final analysis. Results: Mean age of the study subjects was 25.3 ± 4.7 years and their mean casual plasma glucose level was 99.1 ± 16.3 mg/dl. 315 (96.6%) study subjects had casual plasma glucose level of 139 mg/dl or less. Only 10 (3.1%) study subjects had casual plasma glucose levels between 140 to 199 mg/dl. Just one employee, 41 years old, was found to have casual plasma glucose level of 213 mg/dl. Conclusion: In this study, screening of all individuals for diabetes had a very low yield. Recommendation of universal screening for diabetes does not represent a good use of resources and perhaps not costeffective. However, periodic screening of high risk individuals should be warranted. Key words: Diabetes; Screening; Population; Cost-effectiveness